Genomic Findings In Schizophrenia And Their Implications (Open Herald: Periodical of Methodical Research, 2025)
There has been substantial progressin understanding the genetics of schizophrenia over the past 15 years. This has revealed a highly polygenic condition with the majority of the currently explained heritability coming from common alleles of small effect but with additional contributions from rare copy number and coding variants.Many specific genes and loci have been implicated that provide a firm basis upon which mechanistic research can proceed. These point to disturbances in neuronal, and particularly synaptic,functionsthat are not confined to a small number of brain regions and circuits. Genetic findings have also revealed the nature of schizophrenia’s close relationship to other conditions, particularly bipolar disorder and childhood neurodevelopmental disorders, and provided an explanation for how common risk alleles persist in the population in the face of reduced fecundity.Current genomic approaches only potentially explain around 40% of heritability, but only a small proportion of this is attributable to robustly identified loci. The extreme polygenicity poses challengesfor understanding biological mechanisms.The high degree of pleiotropy pointsto the need for more transdiagnostic research and the shortcomings of current diagnostic criteria as means of delineating biologically distinctstrata.It also poses challengesforinferring causality in observational and experimentalstudiesin both humans andmodelsystems. Finally, the Eurocentric bias of genomic studies needs to be rectified to maximise benefits and ensure these are felt across diverse communities. Further advances are likely to come through the application of new and emerging technologies, such as whole-genome and long-read sequencing, to large and diverse samples. Substantive progress in biological understanding will require parallel advances in functional genomics and proteomics applied to the brain across developmental stages. For these efforts to succeed in identifying disease mechanisms and defining novel strata they will need to be combined with sufficiently granular phenotypic data.